Evaluasi Akuntansi Murabahah Berdasarkan PSAK 102 Pada KSPPS BMT Yayasan Baitul Maal Anabanua Kab. Wajo - Sri Fitriani; Azwar Anwar; Samsinar (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2026)
This study aims to evaluate the implementation of murabahah accounting based on PSAK 102/402, which includes the following main aspects: Recognition and measurement, presentation, and disclosure. The subject of this study was KSPPS BMT Yayasan Baitul Maal Anabanua, Wajo Regency, while the focus of the study was murabahah financing and financial statements. The data collection techniques used were interviews and documentation. The data analysis technique used in this study was descriptive qualitative. The technique in this study began with observing data collection including a general description of the company and related documents, presenting data, and drawing conclusions. The results showed that the implementation of murabahah accounting at BMT Yayasan Baitul Maal Anabanua, Wajo Regency was in accordance with PSAK 102/402 in the aspects of measurement and presentation. However, in the recognition aspect, it was not fully in accordance because there was no evidence of delivery of goods as a condition for recognizing murabahah receivables.